Computer Simulation of Scattering Ar+ and Ne+ Ions from the InP(001)<110> surface at Grazing Incidence - Karimov Mukhtorjon Karimberganovich, Kutliev Uchkun Otoboyevich, Matchоnov Khusniddin Jamoladdinovich, Otabaeva Kamola Uchkun Qizi, Otabaev Mekhroj Uchkun O’g’li (International Journal of Advanced Science and Technology, 2020)
The interaction of ions with solid is one of the independent sections of fundamental physics. This interaction can lead to changes in physical properties of solid bodies and creating materials with desired properties. The results of computer simulation on the investigations of the ion scattering processes on the InP(001)<110> monocrystal surfaces under low-energy (1 keV) grazing ion bombardment have been presented. The peculiarities of the mentioned processes have been investigated by computer simulation. We implemented an algorithm where the depth of the reached layer and the impact coordinates of the incident particle were recorded during the computation. This allows tracing the contributions of various atomic layers of the target to scattering. The code provides opportunities of step-by-step tracing of the particle trajectory and performing calculations with arbitrary angular resolutions. It has been shown that the inelastic energy losses of the scattered particles are considerably higher than the elastic ones in a region of glancing scattering. At grazing ion incidence of the scattered particles, the process ion scattering can be explained by semichannel model.